THE ROLE OF LITERATURE IN SHAPING THE CHARACTER OF LEARNER - Wardiah, Dessy (Jurnal Dosen Universitas PGRI Palembang)
Abstract In Indonesia, the education of literature is sometimes ignored andneglected. Since new era of paradigm, literature is treated as non significantsubject of learning, it is considered to be unimportant, useless, and all sorts of noother forms. Education in Indonesia only focuses on meaningful learning ofscience and mathematics. Although it is not expressed verbally, literature isviewed lower than science and mathematics. The willingness to keep forwardscience is failed, because of ignoring literary education. In line with the growingmagnitude of the need for character education now, literary education andlearning needs were designed. Literature is treated as a basic character education.In such context, there should be serious efforts of all components of the nation tobuild a